A new heuristic scheduling method for the make-pack-route problem in make-to-order supply chains. Issue 2 (3rd April 2019) - Du, Mu; Kong, Nan; Hu, Xiangpei
Abstract: To cater to the growing personalized need of customers, increasingly more make-to-order distribution centers consider a two-phase production (i.e. raw material granulation and order packaging) process when making production and routing decisions, especially for time-sensitive commodities. In this article, we extend the production routing problem to the make-pack-route problem (MPRP) to devise production and routing schedules that allow for flexible order composition and ensure in-time delivery. To solve the MPRP, we propose an iterative sequential scheduling heuristic embedded with the local search, which sequentially solves the three corresponding scheduling problems and improves the overall schedule in an iterative manner. Our numerical studies verify that our method can solve practically meaningful instances (e.g. up to 200 orders and 30 items) in an acceptable time duration (i.e. 1 hour). Our studies show an average 11.6% reduction in the total processing cost compared to an ad hoc scheduling method commonly used in practice. Our studies also suggest that our solution method saves more costs with more orders, higher order variety and larger average commodity quantity and variety in each order.